2023
DOI: 10.1039/d3ta03179a
|View full text |Cite
|
Sign up to set email alerts
|

SbSeI and SbSeBr micro-columnar solar cells by a novel high pressure-based synthesis process

Abstract: Van der Waals chalcogenides and chalcohalides have the potential to become the next thin film PV breakthrough, owing to the earth-abundancy and non-toxicity of their components, stability, high absorption coefficient...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The 2D group VA materials (such as phosphene and antimonene) possess small carrier effective mass and high carrier mobility because they are mainly governed by p orbitals. , However, black phosphorus suffers from ambient instability, which would lead to the degradation of device performance. , Studies have shown that 2D Sb-based materials have good stability while maintaining excellent electronic properties. , SbSeBr is a promising Sb-based chalcogenide, whose layered single crystal has been successfully synthesized and applied to the photovoltaic field . Moreover, the strong electronegativity of Se and Br atoms in SbSeBr contributes to its great stability .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2D group VA materials (such as phosphene and antimonene) possess small carrier effective mass and high carrier mobility because they are mainly governed by p orbitals. , However, black phosphorus suffers from ambient instability, which would lead to the degradation of device performance. , Studies have shown that 2D Sb-based materials have good stability while maintaining excellent electronic properties. , SbSeBr is a promising Sb-based chalcogenide, whose layered single crystal has been successfully synthesized and applied to the photovoltaic field . Moreover, the strong electronegativity of Se and Br atoms in SbSeBr contributes to its great stability .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the strong electronegativity of Se and Br atoms in SbSeBr contributes to its great stability . However, the existing studies on 2D SbSeBr predominantly focus on photoelectric, ferroelectric, thermoelectric, and piezoelectric properties, and its application in transistors remains to be studied.…”
Section: Methodsmentioning
confidence: 99%